2022
DOI: 10.1029/2021jc018204
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Submarine Melt and Subglacial Discharge From Observations at a Tidewater Glacier

Abstract: Two main types of freshwater enter the ocean at the termini of tidewater glaciers: submarine melt from ice that melts directly into the ocean, and subglacial discharge from surface melt or precipitation that drains to the bed of the glacier and then into the ocean. These freshwater sources form plumes that rise along the submarine terminus, driving mixing between glacial freshwater and seawater. The dynamics of these plumes affect both submarine melt rates and fjord circulation (e.g., Carroll et al., 2015;Jenk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…With a terminus width of ~1 km and a maximum grounding line depth of 200 m (Sutherland and others, 2019), the dimensions of LeConte Glacier make it a relatively accessible analog for smaller outlet glaciers around the periphery of the Greenland ice sheet. In addition, the springtime oceanic temperature and water column stratification at LeConte Glacier are similar to typical conditions observed in Greenlandic proglacial fjords (Jackson and others, 2022). Throughout the year, the glacial system is exposed to a range of ocean temperatures (4–7°C at depth; Hager and others, 2022) and subglacial discharge (20–350 m 3 s −1 ; Amundson and others, 2020), with outflowing plumes (Motyka and others, 2003) and a recirculation gyre (Kienholz and others, 2019) typically visible in the near-terminus surface waters.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…With a terminus width of ~1 km and a maximum grounding line depth of 200 m (Sutherland and others, 2019), the dimensions of LeConte Glacier make it a relatively accessible analog for smaller outlet glaciers around the periphery of the Greenland ice sheet. In addition, the springtime oceanic temperature and water column stratification at LeConte Glacier are similar to typical conditions observed in Greenlandic proglacial fjords (Jackson and others, 2022). Throughout the year, the glacial system is exposed to a range of ocean temperatures (4–7°C at depth; Hager and others, 2022) and subglacial discharge (20–350 m 3 s −1 ; Amundson and others, 2020), with outflowing plumes (Motyka and others, 2003) and a recirculation gyre (Kienholz and others, 2019) typically visible in the near-terminus surface waters.…”
Section: Introductionsupporting
confidence: 79%
“…Based on the assumption that submarine melt scales with water velocity adjacent to the ice, melt rates near the location of upwelling subglacial discharge plumes are thought to be higher than those away from discharge outlets (Cowton and others, 2015; Slater and others, 2015; Carroll and others, 2016). Recent work, however, has shown that submarine melt rates can be up to two orders of magnitude higher than those predicted by plume-melt theory (Sutherland and others, 2019; Jackson and others, 2020, 2022), which describes the coupling of buoyant plume theory with a three-equation melt parameterization (Holland and Jenkins, 1999; Jenkins, 2011; Cowton and others, 2015), particularly away from the direct influence of discharge plumes.…”
Section: Introductionmentioning
confidence: 99%
“…The relative timing of peaks in discharge and KE hint at a 1-2 day lag between changes in runo↵ and changes in ocean circulation (Fig. 3 B), which could result from inadequate representation of water storage in the glacier runo↵ model (Jansson et al, 2003;Jackson et al, 2022). However, a lag-correlation analysis did not result in higher correlation estimates.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, both also show that dye injected into the domain with the outflow rapidly spread to regions well beyond the outflowing jet. Indeed, dye concentrations (Figure 9) are fairly uniformly spread across the channel in contrast to the velocity field which exhibits significant lateral shear (Jackson et al., 2017, 2022). In addition, there is considerable downward mixing of the dye into the landward flowing lower layer.…”
Section: Discussionmentioning
confidence: 99%